2022
DOI: 10.1177/23779608221145122
|View full text |Cite
|
Sign up to set email alerts
|

To the Question of Vitamin D Network in Type 1 Diabetes and Diabetic Nephropathy in Children Nursed in Ukrainian Endocrinology Unit

Abstract: Background Vitamin D deficiency is a great problem worldwide. Vitamin D plays an essential role in calcium and bone metabolism. Diabetic nephropathy (DN) is a dangerous kidney-related complication of type 1 diabetes (T1D). Aim of the study To evaluate levels of Vitamin D3 in pediatric patients with T1D and DN; to study the dependence between the Vitamin D level and main clinical and laboratory parameters of the disease, that is, duration, complications episodes, albuminuria levels, glomerular filtration rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Other studies found that there is no relation between vitamin D deficiency and age or sex of diabetic patients [37]. In our study, duration of diagnoses of diabetes negatively affects vitamin D levels and this goes with Bassam et al study [38] and Levgeniia Burlaka et al study [39]. Obese and overweight children had more sever vitamin D deficiency (table 2) and this result was in agreement with previous research [35,40].…”
Section: Discussionsupporting
confidence: 93%
“…Other studies found that there is no relation between vitamin D deficiency and age or sex of diabetic patients [37]. In our study, duration of diagnoses of diabetes negatively affects vitamin D levels and this goes with Bassam et al study [38] and Levgeniia Burlaka et al study [39]. Obese and overweight children had more sever vitamin D deficiency (table 2) and this result was in agreement with previous research [35,40].…”
Section: Discussionsupporting
confidence: 93%